Characterisation of a Novel Series of Aprotinin-derived Anticoagulants - Stassen, Jean Marie; Lambeir, Anne-Marie; Vreys, Ingrid; Deckmyn, Hans; Matthyssens, Gaston; Nyström, Åke; Vermylen, Jos (Thrombosis and Haemostasis, 1995)
Upon vascular damage platelet activation and blood coagulation are initiated. Interference at the initial level of the activation of the coagulation cascade can result in effective inhibition of thrombus formation. The in vivo antithrombotic properties of a series of bovine pancreatic trypsin inhibitor mutants (BPTI, aprotinin) 4C2, 7L22, 5L15, 5L15-PEG, 6L15 and 5L84, as described in the accompanying paper, with a combined inhibitory activity on factor Xa, factor VIIa-tissue factor complex, factor XIa and plasma kallikrein were compared to rTAP, r-hirudin, heparin and enoxaparin in a platelet rich thrombosis model in hamsters.Platelet dependent thrombus deposition was quantified by dedicated image analysis after transillumination of the femoral vein to which a standardised vascular trauma was applied. After increasing intravenous bolus injections all tested agents, except for aprotinin, induced a dose dependent decrease of thrombus formation and a concomitant prolongation of the aPTT. From the linear correlation between these two parameters it was found that 5 out of the 6 tested aprotinin analogues, rTAP and r-hirudin completely inhibited thrombus formation at a therapeutical (2- to 3-fold) aPTT prolongation while 4C2, heparin and enoxaparin only inhibited thrombus formation for 40 to 50 percent at a 2-fold aPTT prolongation. Based on the calculated IC50 values for thrombus formation rTAP was found to be the most active compound in this model.It is concluded that acceptable interference at the initial level of the blood coagulation, e. g. within a therapeutical aPTT prolongation, can significantly inhibit platelet deposition at a site of vascular injury.